Peran Pendidikan Dalam Membentuk Perkembangan Emosi Peserta Didik - Soleha, Siti; Nurunnisa, Fitriyah; Rahayu, Sri; Fitriani, Naila Amania; Nurkholis (Innovative: Journal Of Social Science Research, 2025)
The issue discussed is the significance of the role of educators and the learning environment in supporting students' emotional growth, as emotional development significantly impacts social interactions, academic outcomes, and children's mental health. The purpose of this study is to understand how educators play a role in providing guidance, fostering enthusiasm, and nurturing students' emotional development through various positive activities both inside and outside the classroom. The methods employed include observation and triangulation of information from various sources, with an approach that positions educators as liaisons, supporters, assessors, and motivators in children's emotional growth. The study results indicate that teachers play a crucial role in helping students understand, regulate, and control their feelings, as well as developing social skills such as empathy and caring. Furthermore, character education implemented in schools can enhance students' emotional intelligence, ultimately improving their attitudes, discipline, and academic achievement. A supportive school environment also fosters students' emotional well-being, helping them cope with stress and develop positive interpersonal skills. In conclusion, education serves as a primary foundation for students' emotional development by providing appropriate guidance and encouragement, enabling students to regulate their emotions in a positive manner and engage effectively in social interactions